A study on the election factors of ACM Fellow based on the co-authorship relationship - Hailing Zhou; Xiaole Li; Jin Shi; Ming Li; Situ, Lingyun (Malaysian Journal of Library and Information Science, 2023)
Most of past researches on successful scientist groups focused on the winners of international top-renowned awards. ACM Fellow as an academic honor of Computing Machinery field was rarely investigated. This article focuses on the research of the relationship between Fellows’ success and their co-authorship characteristics with previous Fellows. We selected a list of ACM Advanced Member Grades from 2015 to 2020 in 4 sub-domains as the empirical object, then set relevant indicators to indicate the cooperative relationship to analyze the relationship between their cooperation with previous Fellows and whether they can successfully be awarded as Fellows according to the correlation analysis and binary logistic regression method. The results show that the existence of a cooperative relationship with the previous Fellow is indeed beneficial to the Fellow candidate’s selection. The more previous Fellows a candidate works with, the better chance they have of being elected as a Fellow, but the co-growth fellows are the main factor. Moreover, during the cooperation period, the total amount of the candidates’ own publications and the more their own contributions in the cooperation, the more conducive to success. Our results reflect a possible closing of the Fellowship circle, but also correct for biases about honorary award opportunism.